Critical Analysis of Muhammad Yunus’ Building Social Business - Mwemezi, Peter (EDUMALSYS Journal of Research in Education Management, 2023)
This paper critical examine the overview of the idea, ongoing process of social business in Bangladesh as well contrast of social institutions paradigm with other existing business paradigms. For decades a world has been overloaded with poverty, environmental deterioration, as well moral foulness, social welfare institution seem to offer a glimmer of hope. Poverty alleviation has been a difficult issue tacked by government support, international aid agencies as well private agencies. With the respect to the fact that, the issue raised about collective obligation, there have been progressively integrated ambitions aiming at decreasing social together with unfriendly environmental impact of a company. A distinguished scholar and Nobel Peace Laureate Muhammad Yunus commenced joint ventures with transcontinental organization in Bangladesh, his social enterprise approach has received global attention. Some seem to be convinced that there might be solutions ahead these deliberate approaches, depending on more visionary projects placing the social issues in the key activities. The study, revealed that social enterprise is among those resourceful approaches, pressurize the company move from its business as usual along with innovation capacity leading to local market establishment while solving poverty issues.